Plan de negocios para la creación de una empresa de ropa interior para mujeres con sobrepeso en el cantón La Maná provincia de Cotopaxi periodo 2012 -2013 - Medina Robles, Gresia Yanina (2012)
The main purpose of this research is focused on a feasibility study for the implementation of a lingerie company for overweight women in Canton La Maná. This study originated after analyzing the market and find the lack of a lingerie company for overweight women in the field above. In addition to analyzing customer benefits such as purchasing power and high acceptance of our products. These primary factors contributed to initiate a feasibility study to allow the researcher to know the probability of negative or positive implementing a lingerie company for overweight women in Canton La Maná. For the development of this study applied various strategies and techniques that allow to improve the clarity Market research, technical study and study economic and financial analysis. Finally in the conclusion from the financial point of view we could say that the project is viable, showing a total investment of average which indicates that the business is highly profitable.